БОЛАЖАҚ СҮЎРЕТЛЕЎ ӨНЕРИ ОҚЫТЫЎШЫСЫНЫҢ КӘСИПЛИК КОМПЕТЕНЛИЛИГИН ҚӘЛИПЛЕСТИРИЎ МӘСЕЛЕЛЕРИ - Уразимова, Т.В.; Даулетов, С. (FAN va JAMIYAT, 2023)
The article is devoted to the formation of the professional competence of future teachers by means of fine arts. An important role here is played by aesthetic education, which contributes to the intensification of the development of the worldview, intellectual and creative potentials of the person. Therefore, the education process must be based on creating conditions for the upbringing of a creative person who is ready for dialogue, cooperation and co-creation in various spheres of life.